Development of Guided Inquiry-Based Learner Worksheets to Improve Higher Level Thinking Skills of Learners on Redox Reaction Material - Br Tarigan, Endah Putri; Sugiharti, Gulmah (UNDIKMA, 2024)
This research aims to: (1) knowing the level of need for guided inquiry-based Learner Worksheets (LKPD) at Imelda Medan Private High School. (2) to know the design of LKPD based on guided inquiry on redox material. (3) knowing the feasibility of LKPD according to BSNP standards. (4) knowing the improvement of students' higher-level thinking skills and. (5) knowing the students' response to the guided inquiry-based LKPD on redox reaction material that has been developed. This development was carried out using the R&D method with the 4D development model (Define, Design, Develop, Disseminate). The instruments used are interview guidelines, LKPD validation sheets by validators, questionnaire sheets for students' responses to the developed LKPD. The results of this study indicate that the LKPD prepared has met the eligibility criteria according to BSNP standards validated by material experts and media experts who are UNIMED chemistry lecturers by obtaining a percentage value of 88.46% with the criteria